Analysis of Influence of Product Quality and Price on Buyer's Decision - Mukson; Mohamad Badrun Zaman; Syariefull Ikhwan (Journal of Business and Behavioural Entrepreneurship, 2021)
The product's quality and price are two considerations that consumers weigh before making a purchase. With the Gebug milkfish micro, small, and medium enterprises (MSME), as many as 17 businesses in Losari District, Brebes Regency, this study aims to evaluate the impact of product quality and price on customer satisfaction. The participants in this study were 212 Losari District buyers of MSME milkfish products. With a total sample size of 34 consumers, this analysis used the random sampling technique. Quantitative analysis using a survey approach was used in this study. The price variable received a T-count value of 4,196 with a significance value of 0.001 less than 0.05 (0.001 0.05) based on the results of the t-test statistic, and the regression coefficient has a positive value of 0.715, so it can be inferred that the commodity price has a positive impact on buying decisions. The regression coefficient has a negative value of -0.148, and the T-test statistical results of the product quality variable obtained a t-value of -0.748 with a significant value of 0.459 greater than 0.05 (0.459 0.05) that the quality of a commodity has a positive impact on buying decisions. In this research, product quality and price influence buyer decisions for Gebug milkfish in Brebes Regency's Losari District. Since the regression coefficient is negative (-0.148), it can be inferred that product quality positively impacts buying decisions. In this research, product quality and price influence buyer decisions for Gebug milkfish in Brebes Regency's Losari District. Since the regression coefficient is negative (-0.148), it can be inferred that product quality positively impacts buying decisions. In this research, product quality and price influence buyer decisions for Gebug milkfish in Brebes Regency's Losari District.